2009
DOI: 10.1210/en.2008-1641
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Insulin-Like Growth Factor-I Resistance and Diet-Induced Obesity

Abstract: Obesity and type 2 diabetes mellitus are characterized by insulin resistance, reduced bioavailability of the antiatherosclerotic signaling molecule nitric oxide (NO), and accelerated atherosclerosis. IGF-I, the principal growth-stimulating peptide, which shares many of the effects of insulin, may, like insulin, also be involved in metabolic and vascular homeostasis. We examined the effects of IGF-I on NO bioavailability and the effect of obesity/type 2 diabetes mellitus on IGF-I actions at a whole-body level a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 46 publications
4
52
0
Order By: Relevance
“…In contrast to Magel2-null mice, these mutant mice suffer from severe postnatal growth retardation and low fat mass. Similar to calorie restricted lean mice (68,69), MBII-85/SNORD116 mice exhibit reduced serum Igf-I. GH release was not reported in this strain.…”
Section: Magel2 and The Gh Axismentioning
confidence: 65%
“…In contrast to Magel2-null mice, these mutant mice suffer from severe postnatal growth retardation and low fat mass. Similar to calorie restricted lean mice (68,69), MBII-85/SNORD116 mice exhibit reduced serum Igf-I. GH release was not reported in this strain.…”
Section: Magel2 and The Gh Axismentioning
confidence: 65%
“…IGF-1 resistance has been observed in dysmetabolic states 1,20,46-48 such as chronic renal failure, associated with increased compensatory serum IGF-1 aiming at overcoming IGF-1 signaling defects. 49 Chronic renal failure is a prototypical state of reduced IGF-1 sensitivity, 50-52 developing with progressing renal disease and increased binding proteins, and accounting for growth defects or lost responsiveness to the administration of IGF-1, 53 otherwise able to increase glomerular filtration rate, effectively delaying the beginning of hemodialysis. Resistance training improved IGF-1 sensitivity, thus confirming the state of IGF-1 resistance as causal for the described cross-sectional association between higher IGF-1 levels and chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that IGF1 has potential beneficial effects on vasculopathy and glucose metabolism in cardiovascular tissue, [32][33][34] whereas IGF1 reportedly induces vascular remodeling. 35,36 Expression of IGF1R is much higher than that of IR, and increased IGF1R forms hybrid receptors in VSMCs.…”
Section: Discussionmentioning
confidence: 99%